From a topical point of view : dialectic in Anselm of Canterbury's De Grammatico - Boschung, Peter (Studien und Texte zur Geistesgeschichte des Mittelalters, 2006)
This study of Anselm of Canterbury's enigmatic work "De grammatico" provides a perspective both on Anselm's thought and the history of medieval dialectic immediately prior to the renaissance of dialectic in the 12th century. The first part of the book examines Anselm's notion of dialectic and illustrates the role of "De grammatico" in the context of teaching dialectic. The second part of the book remarks the novelty of Anselm's way of treating fallacies and presents a full study of the technique for treating fallacies, its theoretical basis, and its application in the context of dialectic. The third part explores Anselm's theory of signification as it is presented in "De grammatico" and emphasizes its rich metaphysical underpinnings. Each part begins with a presentation of an assessment of the sources as they were available to Anselm, builds the interpretation of Anselm's ideas on this basis, and reflects on the relation of these ideas to 12th Century logical thought.